The Relationship Between BPJS Ownership and the Regularity of Antenatal Care Visits - Anggun Sasmita; Desiska Pricilia Tumatar (Minsight: Midwifery Insight and Innovation Journal, 2026)
Regular antenatal care (ANC) visits are essential to monitor maternal and fetal health during pregnancy and to reduce the risk of pregnancy complications. However, the regularity of ANC visits among pregnant women is still influenced by several factors, including health insurance ownership. This study aimed to analyze the relationship between BPJS ownership and the regularity of antenatal care visits among pregnant women. The study employed a quantitative analytic design with a cross-sectional approach. The population consisted of pregnant women who attended maternal health services at a healthcare facility, with samples selected using a purposive sampling technique. Data were collected through questionnaires and maternal health records, then analyzed using the Chi-square statistical test with a significance level of 0.05. The results showed that pregnant women who owned BPJS were more likely to perform regular ANC visits compared to those without BPJS ownership. Statistical analysis indicated a significant relationship between BPJS ownership and the regularity of antenatal care visits (p < 0.05). BPJS ownership contributes to improving access to maternal healthcare services by reducing financial barriers during pregnancy. These findings highlight the importance of expanding health insurance coverage and strengthening maternal health promotion programs to improve compliance with ANC visits among pregnant women.